Adverse childhood experiences and risk of cancer during adulthood: A systematic review and meta-analysis. (July 2021) - Hu, Zhao; Kaminga, Atipatsa Chiwanda; Yang, Jun; Liu, Jiefeng; Xu, Huilan
Abstract: Background: Research findings on the relationship between adverse childhood experiences (ACEs) and the risk of cancer were inconsistent. Objective: The purpose of this study was to perform a quantitative synthesis of the preceding research findings. Participants and setting: System review and meta-analysis. Methods: Electronic database of PubMed, Embase, Web of Science and Cochrane Library were systematically searched to identify relevant observational studies published not later than September 9, 2020. Specifically, original articles that reported the risk of cancer in adult populations that experienced ACEs before the age of 18 were selected. All pooled odds ratios (ORs) and 95 % confidence intervals (CIs) were calculated using a random-effects model. Publication bias was examined using funnel plots, and sensitivity analysis was used to explore the stability of the pooled results. Results: A total of 18 studies involving 406, 210 participants were included in this review. Individuals with 2 or 3 kinds of ACEs (OR = 1.35, 95%CI:1.12, 1.62) or at least 4 ACEs (OR = 2.17, 95%CI: 1.76, 2.68) were at increased risk of cancer when compared with individuals with no ACEs. Of the different types of ACEs examined, physical abuse (OR = 1.23, 95%CI:1.05, 1.43), sexual abuse (OR = 1.26, 95%CI:1.02, 1.56), exposure to intimate partner violence (OR = 1.26, 95%CI:1.12, 1.41) and financial difficulties in the family (OR = 1.16, 95%CI:1.00, 1.33) were associated with the risk of any cancer. Conclusions: These findings suggest that multiple ACEs may be a risk factor for cancer development. Therefore, prevention of ACEs and interventions for supporting those affected by ACEs are necessary.